Knowledge acquisition by SMEs in weak client-firm exchange relationships - Geneste, Louis André (Curtin University, 2010)
This thesis examines the role that non-collaborative, weak exchange relationships might play in the acquisition of knowledge by small and medium-sized enterprises (SMEs). An important source of knowledge for a firm lies in its network of relationships. There has been considerable research conducted on knowledge transfer and acquisition through linkages, such as strategic alliances and similar-type, close collaborations with other businesses. However, many SMEs are less likely to be involved in collaborative, close interfirm relationships because of their relatively small market share, short industry time and uncertainty associated with the firm's future. Consequently, much of the research on interfirm relationships has overlooked SMEs. Many SME linkages are the non-collaborative, arm's-length type that many researchers argue play very little or no role in knowledge transfer and acquisition. However, research has found that inter-firm relationships that are not close and less collaborative are a source of new external knowledge.This doctoral study researches the value of weak, arm's-length client ties to the SME in terms of the knowledge they could impart to the firm. The extent to which this acquired knowledge leads to knowledge-related outcomes, such as new product and market development, increased operating efficiency and innovative performance, are also examined. Factors posited to lead to knowledge acquisition in these weak exchange ties include the SME owner's efforts at building more long-term relationships and efforts at signalling the SME's reputation and legitimacy. Also posited to lead to knowledge acquisition is the trust of the arm's-length client. The study also examines factors posited to contribute to the knowledge-based outcomes derived from the knowledge acquisition. The factors include absorptive capacity and exchange partner similarity and are hypothesized to moderate the relationship between knowledge acquisition and knowledge outcomes. Other moderating factors include the size and age of the client firm and the growth intentions of the SME owner.To conduct this research, a cross-section of Western Australian SMEs was surveyed through the WA Small Business Benchmark Survey undertaken by Curtin's School of Management. A paper-based version of the survey was administered to a Dan & Bradstreet database of 10,000 small and medium-sized enterprises. Additionally, an on-line version of the survey was also sent to SMEs via a range of small business associations across Western Australia. Low response rates are common in SME research and this study is no exception. Just over 400 businesses responded to the survey, of which 298 respondents completed the survey questions pertaining to the thesis study.A model explaining the interrelationships of factors and paths leading to knowledge acquisition and knowledge outcomes was analysed. Exploratory and confirmatory analyses of the data were carried out and structural equation analysis examined the fit of the model to the data. Based on the results, the measure of the relationship strength of the client-firm tie could not be verified. However, it was found that trust of the client in exchange relationships led to knowledge acquisition but reputation signalling and relationship initiation seemed more related to marketing efforts and did not contribute significantly to knowledge acquisition. Knowledge acquisition was significantly associated with knowledge-based outcomes and absorptive capacity, as well as exchange partner similarity, which partly moderated the extent to which knowledge based outcomes were derived from acquired knowledge. The growth intentions of the SME owner could not be verified as a moderator and the size of the client firm was not found to have a moderating effect. The findings are tempered by the small sample size and the low response rate so generalising these findings to the broader WA SME population would be inappropriate. However, the study did reveal the relative importance of absorptive capacity and exchange partner similarity in the conversion of acquired knowledge to knowledge-based outcomes. These findings encourage further research and more analyses to verify the role of absorptive capacity and exchange partner similarity in client-firm exchange relationships.